1983
DOI: 10.1002/hlca.19830660509
|View full text |Cite
|
Sign up to set email alerts
|

The Radical Anions of Some Benzo‐Derivatives of Dehydrocyclooctatetraenes

Abstract: In memory of Professor Franz Sondheimer (6.V. 83) SummaryThe radical anions of 5,6-didehydrobenzocyclooctene (3), 5,6,9,10-tetradehydrobenzocyclooctene (4) and 1,4,7,10-tetramethy1-5,6-didehydrodibenzo [u, el-cyclooctene (6) were prepared in situ from dibromo-precursors and have been characterized by ESR and ENDOR spectroscopy.Introduction. -Dehydrocyclooctatetraenes and their benzo-derivatives have received much attention in the last few years [I]. Insertion of a triple bond into the unsaturated eight-membere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Unfortunately, 3 and its anion radical are unknown. However, the anion radical of 3,4-benzo-[8]annulyne at ambient temperature was reported 1 For the anion radials of [8]annulyne and benzo-[8]annulene, the B3LYP/6-31G*-predicted carbon p z spin densities (shown in parentheses) are in extraordinary agreement with the experimental spin densities obtained from the a H values and the McConnell relationship ( a H = Q ρ with Q = 25.6 G).…”
supporting
confidence: 59%
“…Unfortunately, 3 and its anion radical are unknown. However, the anion radical of 3,4-benzo-[8]annulyne at ambient temperature was reported 1 For the anion radials of [8]annulyne and benzo-[8]annulene, the B3LYP/6-31G*-predicted carbon p z spin densities (shown in parentheses) are in extraordinary agreement with the experimental spin densities obtained from the a H values and the McConnell relationship ( a H = Q ρ with Q = 25.6 G).…”
supporting
confidence: 59%
“…The radical anions of 11a and 12 were generated in solution through the corresponding neutral species prepared in situ and were characterized by ESR and ENDOR spectroscopy. [22] For doubly benzo-annelated systems, there are two possible modes of fusion; one is an a,e-fusion such as didehydroannulene 13a and tetradehydroannulene 14a (of D 2h point group) and the other is a C 2v symmetric a,c-fusion such as 15. While initial attempts to prepare 15 gave no reasonable evidence for its existence, [23a] its formation was later supported by the interception of its [4+2] adduct with a diene in the synthesis of cyclic phenylenes.…”
Section: Strained Dehydrobenzo[8]annulenes ([8]dbas)mentioning
confidence: 99%
“…Note that both one-electron and two-electron reductions of 13a by alkali metal or by cyclic voltammetry could be carried out to form its radical anion and dianion (a 10π-electron system), respectively, while only one-electron reduction of 14a could be performed because irreversible polymerization took place upon further reduction. [24b,36] The radical anions of 13a, [37] 13b, [22] and 14a [37] thus formed were characterized by ESR spectroscopy. Cp*Co-cyclobutadienefused derivative 19 was isolated by Vollhardt during an attempt to synthesize [4]phenylene and its X-ray analysis revealed that the eight-membered ring is planar and the triple bond slightly less deformed [23.0°(average)] than that of 13a.…”
Section: Strained Dehydrobenzo[8]annulenes ([8]dbas)mentioning
confidence: 99%